Assessing quality of life in Alzheimer's disease: Implications for clinical trials. Issue 1 (13th December 2016) - Kahle‐Wrobleski, Kristin; Ye, Wenyu; Henley, David; Hake, Ann Marie; Siemers, Eric; Chen, Yun‐Fei; Liu‐Seifert, Hong
Abstract: Introduction: Characterization of the quality of life (QOL) in Alzheimer's disease (AD) scale within the context of a clinical trial may inform its applicability in future trials. Methods: Using data from 1322 patients enrolled in two phase‐III studies (EXPEDITION 1 [NCT00905372 ] and 2 [NCT00904683 ]) of intravenous solanezumab in outpatients with mild AD dementia, correlations between patient‐ and caregiver‐assessed QOL and between QOL and clinical outcome measures were examined. Longitudinal effects of solanezumab over 80 weeks were explored, controlling for patient and caregiver baseline characteristics. Results: Caregivers rated patients' QOL worse than did patients themselves. Patients' QOL was correlated, albeit modestly, with clinical/health measures. Patients' QOL changed minimally over 80 weeks, although a treatment effect of solanezumab on QOL was detected. Discussion: Further investigations are needed to determine the optimal measures with which to quantify and qualify QOL of patients with mild AD.